Neuquén : Comparación Censo Nacional Agropecuario 2002-2018 - Ejarque, Mercedes; Lammel, Sofía Ailén; Perez Centeno, Marcelo; Gigena Iturbe, Conrado (2025)
Datos del Censo Nacional Agropecuario 2018 (INDEC)